Marine Drug Research in China: Selected Papers from the 15-NASMD Conference - Zhou, Xuefeng; Luo, Xiaowei; Liu, Yonghong (2022)
The Book covers this whole field, from the discovery of structurally new and bioactive natural products (including biomacromolecules), from marine macro-/micro-organisms, to the pharmacodynamics, pharmacokinetics, metabolisms, and mechanisms of marine-derived lead compounds, both in vitro and in vivo, along with the synthesis and/or structural optimization of marine-derived lead compounds and their structure-activity relationships. Taken together, this Special Issue reprint not only provides inspiration for the discovery of marine-derived novel bioactive compounds, but also sheds light on the further research and development of marine candidate drugs.